2013
DOI: 10.3354/meps10414
|View full text |Cite
|
Sign up to set email alerts
|

Foraging closer to the colony leads to faster growth in little auks

Abstract: Knowledge of foraging behaviour is essential to understand both the ecological roles of seabirds and the constraints acting upon them in marine ecosystems. Here, we investigated foraging trips of a small planktivorous alcid, the little auk Alle alle, using miniature GPS loggers. We performed the study in 2 large breeding colonies in west Spitsbergen (Hornsund and Magdalenefjorden) with contrasting oceanographic conditions (Arctic and Atlantic environments, respectively). Generally, in both locations little auk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 70 publications
7
65
1
Order By: Relevance
“…This was also the basis for our assumption that in examining the larger Calanus fraction obtained from LOPC measurements we were mainly determining the older life stages of C. glacialis in the Arctic Zone and of C. finmarchicus in the Atlantic Zone. The net zooplankton catches described by Jakubas et al (2013) in the same area (Arctic-type waters, the Hornsund area) and at the same period as our study (the end of July) showed that C. glacialis represented 70% of the older life stages (CIV, CV and adults) of both mentioned Calanus species and that the fifth copepodite of C. glacialis constituted half of this amount. Moreover, multiyear observations conducted by Kwasniewski et al (2012) showed the substantial domination of C. glacialis older copepodite stages over C. finmarchicus in the Arctic shelf community at this time of the year.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This was also the basis for our assumption that in examining the larger Calanus fraction obtained from LOPC measurements we were mainly determining the older life stages of C. glacialis in the Arctic Zone and of C. finmarchicus in the Atlantic Zone. The net zooplankton catches described by Jakubas et al (2013) in the same area (Arctic-type waters, the Hornsund area) and at the same period as our study (the end of July) showed that C. glacialis represented 70% of the older life stages (CIV, CV and adults) of both mentioned Calanus species and that the fifth copepodite of C. glacialis constituted half of this amount. Moreover, multiyear observations conducted by Kwasniewski et al (2012) showed the substantial domination of C. glacialis older copepodite stages over C. finmarchicus in the Arctic shelf community at this time of the year.…”
Section: Discussionmentioning
confidence: 52%
“…We decided to broaden the size range for Calanus spp. suggested by Basedow et al (2010) to the upper limit applied by Jakubas et al (2013), who combined net sampling together with LOPC measurements taken together at the same time in the research area. The Calanus size fraction classified as the size range of 1-2.5 mm according to Jakubas et al (2013) and Trudnowska et al (2014) was composed of Calanus spp.…”
Section: −3mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the thin-billed prion chicks, showing an increase in the relative number of heterophils and the H/L ratios with age, experienced poor feeding conditions (Quillfeldt et al 2008). The study area (Magdalenefjorden) is generally considered a suboptimal feeding ground, with a prevalence of warmer water masses that affect the birds' foraging behaviour and chick growth (Kwasniewski et al 2010;Jakubas et al 2011Jakubas et al , 2013. A study comparing body mass and the H/L ratio in little auk chicks between the colony investigated in the present study and in Hornsund (SW Spitsbergen) showed no differences in those variables in a year when the food supplied was of similar quantity and quality .…”
Section: Discussionmentioning
confidence: 99%
“…However, after the realimentation period from 22 to 42 days of life, there were no significant differences in leucocyte profiles and body mass between food-restricted and ad libitum chickens. Little auk parents are capable of intensifying their parental efforts under suboptimal food conditions (Harding et al 2009;Jakubas et al , 2011Jakubas et al , 2013Kwasniewski et al 2010) and can increase their provisioning effort. It is hypothesised that such a reaction is triggered by the increased begging behaviour in chicks with an elevated corticosterone level (Kitaysky et al 2003), which is related to the H/L ratio (Davis et al 2008).…”
Section: Discussionmentioning
confidence: 99%